Akurasi Data Koordinat Atlas Der Gehele Aarde Dalam Penentuan Arah Kiblat: Studi Kasus BHRD Kabupaten Tegal - Naelul Marom; Ahmad Izzuddin (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
The determination of the Qibla direction in Indonesia ideally utilizes precise local coordinate data. However, the Board of Hisab and Rukyat (BHRD) of Tegal Regency employs a unique method by using coordinate data derived from the